Incidence of Multidrug-resistant Tuberculosis in Sindh, Pakistan - Khan, Rashid A (Cureus, 2019)
Introduction Pakistan carries a high burden of pulmonary tuberculosis. Resistance to anti-tuberculosis drugs is increasing rapidly in this region. The purpose of this study is to determine the incidence of multidrug-resistant tuberculosis (MDR-TB) in Sindh, Pakistan. Methods We conducted a prospective, observational study in the department of pulmonology at Civil Hospital, Jamshoro. A total of 169 patients with smear-positive sputum after two months of compliant therapy with first line anti-tuberculosis therapy (ATT) were included in the study. Drug susceptibility testing was performed; this involved the preparation and testing of a concentration series of drugs against the Mycobacterium (M.) tuberculosis complex. Data were analyzed using Statistical Package for the Social Sciences (SPSS) software Version 18.0 (SPSS Inc., Chicago, US). Results Overall, the frequency of MDR-TB patients being treated with first-line ATT was 40.2% (68/169). Among these cases of MDR-TB, there were 36 (53%) men and 32 (47%) women. The most common second-line drug resistance was to ofloxacin (43.2%; n=73). Conclusions The growing drug resistance of M. tuberculosis is a problem in Pakistan, and measures should be taken to reduce the incidence of resistance, including increasing patient compliance to therapy.